Application of Electron Accelerators for X-ray Fluorescence Element Analusis; 3rd International Congress on Radiation Physics and Chemistry of Condensed Matter, High Current Electronics and Modification of Materials with Particle Beams and Plasma Flows - Bespalov V. I. Valery Ivanovich; Krechetov Yu. F. Yuri Fedorovich; Lazarenko S. E. Svetlana Evgenjevna; Shuvalov E. N. Evgeny Nikolaevich; Uglov S. R. Sergey Romanovich (2012, 2012)
Title screen.